Comparison of arthroscopic capsule release and manipulation under anaesthesia for frozen shoulder: a prospective randomized single blinded interventional study - Arvind; Singh, Gurchetan; Sudarshan, Pavan (International Journal of Research in Orthopaedics, 2025)
Background: Adhesive capsulitis (frozen shoulder) is a common cause of shoulder pain, affecting approximately 2% of the population. Despite its prevalence, the exact aetiology remains unclear, leading to varied treatment protocols. Among the available interventions, manipulation under anaesthesia (MUA) and arthroscopic capsular release (ACR) are widely used for refractory cases, though comparative data on their outcomes are limited. Aim: To compare early clinical outcomes, complications and pain relief between MUA and ACR in patients with refractory adhesive capsulitis. Methods: A prospective, randomized, single-blinded study was conducted from November 2020 to April 2022 at a tertiary care hospital. Forty-four patients with refractory adhesive capsulitis were randomized into two groups: MUA (n=22) and ACR(n=22). Preoperative evaluations included clinical and ultra-sonographic examinations. Postoperative outcomes were assessed at 2, 4 and 12 weeks using the Visual Analogue Scale (VAS), Oxford Shoulder Score (OSS) and range of motion (ROM) measurements. Results: Both groups demonstrated significant improvements in pain and ROM. However, ACR yielded superior results, with a greater reduction in VAS scores (8 to 1in ACR vs. 8 to 3 in MUA) and better ROM at 12 weeks. Forward flexion improved from80º to 180º in the ACR group, compared to 70º to 170º in the MUA group. External and internal rotation improvements were also significantly greater in the ACR group. Conclusions: Arthroscopic capsular release, combined with an exercise regimen, provides significantly better pain relief and functional recovery compared to MUA in refractory adhesive capsulitis.